Long-Term Conservation Tillage Increases Yield and Water Use Efficiency of Spring Wheat (Triticum aestivum L.) by Regulating Substances Related to Stress on the Semi-Arid Loess Plateau of China - Changliang Du; Lingling Li; Junhong Xie; Zechariah Effah; Zhuzhu Luo; Linlin Wang (Agronomy, 2023)
Improving the water-use efficiency (WUE) of crops is the most effective way to increase yields in semi-arid regions. Field research was carried out based on a long-term experiment initiated in 2001, aimed to explore the mechanisms of different tillage practices effects on grain yield and WUE of spring wheat. Tillage practices in the research including conventional tillage (CT), no tillage with no straw mulching (NT), conventional tillage with straw incorporation (TS), and no tillage with straw mulching (NTS). The effects of tillage practices on soil’s physical and chemical properties, dry matter accumulation, grain yield, dynamics of stress-related substances, and WUE were observed. Soil and plant samples in this research were collected in 2020 (wet year), 2021 (dry year), and 2022 (dry year). The results indicated that NTS improved the soil’s physical and chemical properties. The NTS treatment had the lowest soil bulk and pH and the highest total N, NO3--N, and available P. Throughout the whole growth stage, soil water content in the NTS and TS treatments were significantly higher than that of CT by 8.77–20.40% and 2.19–18.83, respectively. Averaged catalase (CAT), peroxidase (POD), and soluble protein across the three years with NTS and TS were significantly increased by 1.26–25.52% compared to CT. Meanwhile, the NTS treatment had the lowest malondialdehyde (MDA) content among the different tillage practices. NTS maintained the highest dry matter accumulation throughout the whole growth stage among different treatments; it was increased by 10.47–73.33% compared with CT. The average grain yields and WUE of NTS across the three years were 6.09–30.70% and 6.79–40.55% higher than other tillage practices, respectively. It is concluded that NTS influences dry matter accumulation and water-use efficiency during the whole growth stage of spring wheat by improving the soil’s physicochemical properties and modulating spring wheat substances related to stress, which in turn promotes yield formation.